Kewenangan Badan Pengelola Keuangan Daerah dalam Pengendalian Pelaksanaan Anggaran Pendapatan dan Belanja Daerah (Studi Pada Pemerintah Daerah Tulang Bawang) - Noviasih Muharam (Law Faculty of Universitas Bandar Lampung, 2016)
As according to Government Regulation Number 41 Year 2007 about region ware organization, so it is published a Government Regulation of Lampung Province Number 9Year 2007 about the formation of finance office administration organization of Lampung Province. Based on explanation above, so that be troubleshoot in this research is how does Finance Office Authority of Lampung Province in management and control towards Revenue Plan Execution and Region Expense (APBD) at Lampung Province. This research Method uses a judicial normative and empirical approach. In carry out the function as Region Finance Official Manager (PPKD), so Province Finance Office must give warning to various related parties related to Revenue Plan Execution and Region Expense (APBD) like Region Ware Work Unit (SKPD) with do socialization with submit estimation management communicatively to each Region Ware Work Unit (SKPD). Local government on the contrary do anticipative action in takes wisdom to avoid deficit estimation with balances between income and region expense.